He's a Chip Off the Old Block - The Persistence of Occupational Choices Across Generations - Bodo Knoll; Nadine Riedel; Eva Schlenker (Center for Economic Studies and ifo Institute (CESifo), 2013)
The purpose of this paper is to assess intergenerational occupational mobility in Germany. Using data from the Socioeconomic Panel (SOEP), we find a high persistence of occupational choices across fathers and children. To separate effects related to parental advice and influence (nurture) from genetic factors (nature), we determine the persistence separately for children who grew up with their biological fathers and those who did not. The results suggest that nurture-related effects explain a significant fraction of the observed correlation of fathers' and children's occupational choices. We discuss policy implications that follow from the analysis.
Keywords: J24; J62; 330; occupational choice; German SOEP; parental educational investment